2020
DOI: 10.3390/agriculture10040115
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating the Effects of Habitat Loss on Solitary Bees in Agricultural Ecosystems

Abstract: Solitary bees and other wild pollinators provide an important ecosystem service which can benefit both the agricultural economy and the sustainability of many native ecosystems. Many solitary bees, however, are experiencing decreases in their populations and ranges, resulting in an overall loss of pollinator species richness in many areas. Several interacting factors have been implicated in this decline, including increased pesticide use, climate change, and pathogens, but habitat loss remains one of the prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 101 publications
1
29
0
Order By: Relevance
“…The behavior of spending the night inside the nest herein described was also observed in the two previous study with E. dejeanii (Hiller & Wittmann, 1994;Dec & Vivallo, 2019). By spending more time away from the nest, the female bee leaves it more vulnerable to predators and parasites (Kline & Joshi, 2020). Despite the activity of parasites and predators of bee nests is more intense during the day (Kelber et al, 2005), the behavior of females in spending the night inside the nest could be related to a more effective strategy in protecting their nests.…”
Section: Nesting and Foraging Behaviorsupporting
confidence: 79%
“…The behavior of spending the night inside the nest herein described was also observed in the two previous study with E. dejeanii (Hiller & Wittmann, 1994;Dec & Vivallo, 2019). By spending more time away from the nest, the female bee leaves it more vulnerable to predators and parasites (Kline & Joshi, 2020). Despite the activity of parasites and predators of bee nests is more intense during the day (Kelber et al, 2005), the behavior of females in spending the night inside the nest could be related to a more effective strategy in protecting their nests.…”
Section: Nesting and Foraging Behaviorsupporting
confidence: 79%
“…It has been demonstrated that the abundance of wild bees and their diversity in habitats such as farms depend not only on the quality of the farms but also on the distance between the nesting habitats and the patches of their foraging habitat (Ekroos et al 2013;Gathmann et al 1994;Ricketts et al 2008;Steffan-Dewenter and Schiele 2008). In addition to a sufficient amount of nesting habitat, a landscape should provide sufficient floral resources for pollinators (Kline and Joshi 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Habitat loss and fragmentation make it challenging to find nesting sites and floral resources because bees need their nesting and floral habitats to be adjacent (Kline and Joshi 2020). Habitat loss affects the abundance and diversity of pollinators mainly because of decreasing floral resources (Winfree et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations